Promoting rational antibiotic prescribing for non-complicated infections: understanding social influence in primary care networks in Germany - Poß-Doering, Regina; Kamradt, Martina; Glassen, Katharina; Andres, Edith; Kaufmann-Kolle, Petra; Wensing, Michel (BMC family practice, 2020)
Primary care networks in Germany are formalized regional collaborations of physicians and other healthcare providers. Common goals are optimized healthcare processes and services for patients, enhanced communication, agency for professional concerns and strengthened economic power. In the ARena study (Sustainable reduction of antibiotic-induced antimicrobial resistance), 14 primary care networks in two federal German states aimed to promote appropriate antibiotics use for acute non-complicated infections by fostering awareness and understanding. Factors related to the role of primary care networks were to be identified.
Gesehen am 21.04.2020